Wolbachia Infection Alters the Microbiota of the Invasive Leaf-Miner Liriomyza huidobrensis (Diptera: Agromyzidae) - Ya-Xin Duan; Ying-Hua Zhuang; Yu-Xin Wu; Tian-Wei Huang; Zhang-Rong Song; Yu-Zhou Du; Yu-Xi Zhu (Microorganisms)
Microbe–microbe interactions within a host drive shifts in the host’s microbiota composition, profoundly influencing host physiology, ecology, and evolution. Among these microbes, the maternally inherited endosymbiont Wolbachia is widespread in the invasive pest Liriomyza huidorbrensis (Diptera: Agromyzidae). However, its influence on the host microbiota remains largely unexplored. In the study presented herein, we investigated the bacterial communities of Wolbachia wLhui-infected (wLhui+) and -uninfected lines (wLhui−) of L. huidorbrensis using 16S rRNA gene high-throughput sequencing. For both leaf-miner lines, Bacteroidota was the dominant phylum (relative abundance: 59.18%), followed by Pseudomonadota (36.63%), Actinomycetota (2.42%), and Bacillota (0.93%). We found no significant differences in alpha-diversity indices between the wLhui+ and wLhui− lines (p > 0.05). However, principal coordinates analysis revealed significant differences in microbiota composition between the wLhui+ and wLhui− lines (PERMANOVA: p < 0.001), explaining 76.70% of the variance in microbiota composition. Correlation network analysis identified robust negative and positive associations between Wolbachia and several genera, suggesting that Wolbachia shapes microbial composition through competitive or cooperative interactions with specific taxa. Overall, our study suggests that Wolbachia plays a key role in shaping the leaf-miner microbiome, potentially affecting host fitness.